2020
DOI: 10.1177/1468087420940942
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of the performance, emission and combustion stability of compression ignition engine powered by diesel and ammonia solution (NH4OH)

Abstract: This study presents experimental examinations of a stationary single-cylinder compression ignition dual fuel engine for the combustion of diesel fuel with water ammonia solution. The effect of 25% water ammonia solution on the combustion, performance, emissions and stability of the dual fuel compression ignition engine was investigated, taking into account its different operating conditions. The experiments were carried out for three modes of engine operation with three loads (35%, 60% and 100%) and a change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Nonetheless, a noticeable decrease in the brake and specific fuel consumption of the engine is observed. However, HC and CO emission levels are increased with the augmentation of the WAS in the blend due to the incomplete combustion of the fuel mixture [16]. It can be understood from the present literature review that mixing WAS with GF in SI engine improves engine performance and increases harmful emissions.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…Nonetheless, a noticeable decrease in the brake and specific fuel consumption of the engine is observed. However, HC and CO emission levels are increased with the augmentation of the WAS in the blend due to the incomplete combustion of the fuel mixture [16]. It can be understood from the present literature review that mixing WAS with GF in SI engine improves engine performance and increases harmful emissions.…”
Section: Introductionmentioning
confidence: 72%
“…It is well established that ammonia derived from renewable energy sources will provide a green-originated carbon free fuel [11]. To improve combustion, the blends of ammonia solution and GF were used to optimize the engine's performance [16]. Ammonia has enormous promise as a substitute for petroleumbased fuels.…”
Section: Ammonia Solution -Gasoline Blends Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that 10% wt NH3 in methanol is a suitable mixture ratio due to having lower CO2 emission. Pyrc et al [10] investigated experimentally the effects of diesel-NH3 solution (NH4OH) on performance, emission and combustion stability by using compression ignition engine. They revealed that the advantages of NH3 as a fuel against harmful emission gases.…”
Section: Introductionmentioning
confidence: 99%